Cystic Changes of Breast in a Family With Autosomal Dominant Polycystic Kidney Disease (Iranian Journal of Kidney Diseases, 2009)
Autosomal dominant polycystic kidney disease is associated with cysts in many organs including the liver, pancreas, lungs, spleen, ovaries, testes, thyroid, and uterus. However, there is no report, to our knowledge, of cystic changes of the breast along with this disease. We describe 3 members of a family with multiple bilateral breast cysts in association with autosomal dominant polycystic kidney disease.